IDENTIFYING SPATIAL CHARACTERISTICS OF TRANSMISSIVITY USING SIMULATED ANNEALING AND KRIGING METHODS - Lin Yu.P.; Tan Y.Ch.; Rouhani Sh. (My University, 2001)
Groundwater flow and transport modeling require proper and accurate hydrogeological properties. These hydrogeological data, including information on transmissivity or hydraulic conductivity, may contain significant uncertainty, displaying complex spatial variation. This study identified the spatial patterns and variations in transmissivity in the southeast of Yun-Lin County and the north of Chia-Yih County in Taiwan to reveal the spatial characteristics of hydrogeological formation for groundwater study. The spatial maps of transmissivity were estimated and simulated using ordinary kriging and simulated annealing methods. Correlation analysis revealed that realizations of simulations could fully display the characteristics of transmissivity within this study area. Correlation analysis also indicated that both estimation and simulation results displayed similar patterns. The spatial maps of the estimation and simulation of transmissivity indicated that simulated annealing could not only reproduce the statistics and spatial variation of the measured transmissivity, but could also identify the global spatial continuity patterns of transmissivity. The simulated maps of transmissivity also fully illustrate the characteristics of the geological and aquifer characteristics of the study area.
Keywords: TRANSMISSIVITY; SIMULATED ANNEALING; ORDINARY KRIGING; SPATIAL CHARACTERISTICS